Citizen participation and decision-making under martial law administration a search for a viable political system - De Guzman, Raul P. (Philippine Journal of Public Administration, 1977)
The political changes established under martial law represent a search for suitable alternatives to the old arrangements. What is emerging as a new political system is described, analyzed and evaluated in this paper by focusing on citizen participation using Western democracy as baseline, and on decision-making by technocrats and administrators, with case illustrations on foreign investments, the local tax code, and reorganization. The implications of such arrangements are examined in depth.